Deteksi residu antibiotik pada telur ayam layer di peternakan ayam layer di Sesaot Lombok Barat - Abdul Aziz; Alfiana Laili Dwi Agustin; Candra Dwi Atma (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
Eggs are a source of animal protein that is cheap and easy to obtain by the community besides having a good taste and also eggs have complete nutrition. However, one of the problems that can harm consumers when consuming chicken eggs is the presence of antibiotic residues that offer antibiotics that are not right or not according to the procedure. cause residues in large amounts and cause side effects, which are very detrimental in terms of health, such as the most important allergies and can even cause resistance. This study aims to see no antibiotic residue in the layers of chicken eggs from layer chicken farms in Sesaot Narmada, West Lombok. The results of testing samples from 10 samples of layer chicken eggs Layer chicken farms in sesaot Narmada West Lombok which were tested using the Bioassay Screening Test method showed negative results containing antibiotic residues. Negative results after testing the antibiotic residues in the entire sample Layer chicken eggs in layer chiken pruttny in the village of Sesaot farms, Narmada district, West Lombok Regency, showed negative results. Negative results in every event with no inhibition zone formed around the disc paper containing the layer chicken egg sample and only the inhibition zone formed on the positive control disc paper on the Bioassay Screening Test tester. of the four classes of antibiotics including macrolides, aminoglycosides, Tetracycline and penicillin.